Refining the workflow of a web survey management application - Carlén, Filip; Forsvall, Hampus; Persson, Simon; Tholén, Erik (My University, 2015)
This bachelor thesis describes the process of improving the workflow for marketing analysts creating online questionnaires by supplementing the currently used legacy software with a new web application. The goal is to reduce time spent on creating questionnaires in order to allow for more time analyzing the results. Design of graphical user interfaces (GUI) is an area of research in constant change, regularly affected by new trends. This causes existing design to quickly become outdated, sometimes greatly affecting the usability of the applications behind them. The workflow was improved by first analyzing the existing software and its shortcomings in terms of user experience (UX), and then developing a new application with these in mind. The new application would allow for a better workflow along with new features that the existing software did not have, e.g generating documents compatible with Microsoft® Word and storing commonly used questionnaires in a database for later reuse. The result is a web application called QuestBuilder that can be accessed through a web browser. The application is tailored to the needs of marketing analysts and offers a handful of new features. The application is considered a prototype and therefore does not cover all features from the old software. However the features that are implemented offer a significantly improved workflow compared to the old software.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science